Pemberdayaan Ibu-Ibu Rumah Tangga di Mojomulyo, Sragen Kulon, Kabupaten Sragen melalui Usaha Telur Asin Aneka Rasa - Ratih Dewanti; Ari Kusuma Wati; Lilik Retna Kartikasari (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2020)
Salted eggs are very potential to be used as a cheaper source of animal protein compared to meat. Salted eggs of various flavors have not been popular in Sragen Regency, so they have the prospect of being developed as a new culinary. Housewives in Mojomulyo, Sragen Kulon, Sragen Regency who are members of the social gathering of neighborhoods have a lot of free time. The problem was that they need additional income from their own home business which could be part-time besides their main duties as a housewife. Salted eggs of various flavors were salted eggs which were given additional flavors, that was the taste of soto, onion, durian, curry, spicy, chocolate, and strawberry. It was hoped that with the diversification of salted eggs, it can increase the target of consumers, especially children, and children can more easily obtain sources of animal protein because they like eating eggs. Eggs that were salted and made of various flavors were duck eggs, chicken eggs and quail eggs. Community service activities include counseling activities, the practice of making salted eggs, the practice of making salted eggs of various flavors, simple bookkeeping, packaging and marketing of products. This community service activities was useful for increasing the knowledge and utilizing their free time of housewives in Mojomulyo. Through this activity, the abilities and skills of housewives in Mojomulyo have increased and were expected to be economically independent.